Electrical characterizations of PVC-LiTFSI Al2O3 (99% Gamma 40-80 nm) polymer electrolyte / Muhamad Kamarul Azman Sulaiman. - Sulaiman, Muhamad Kamarul Azman (2008)
In this study of nanocomposite polymer electrolyte, Poly vinyl chloride, (PVC), was used as the host polymer and lithium (bis) trifluoromethanesulfonimide, (LiTFSI), as the doping salt with Aluminium Oxide, Al2O3 as the filler. PVC and salt in different weight % concentrations dissolved in Tetrahydrofuran, (THF). The influence of different concentration of salt on PVC gave rise to different values of ionic conductivity. The best conductivity concentration of PVC-LiTFSI was mixed with various weight % of Aluminium Oxide in nanosize to form PVC-UTFSI-Al2O3 nanocomposite polymer electrolytes. The ionic conductivity of nanocomposite polymer electrolyte was determined by impedance spectroscopy. Temperature dependence of conductivity behavior of the best conducting PVC-LiTFSI and PVC-LiTFSI-Al2O3 samples was also investigated to obtain the values of activation energy (Ea) of conduction.